2011
DOI: 10.1073/pnas.1112378108
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic regulation of cortical UP states

Abstract: The synchronization of neuronal assemblies during cortical UP states has been implicated in computational and homeostatic processes, but the mechanisms by which this occurs remain unknown. To investigate potential roles of astrocytes in synchronizing cortical circuits, we electrically activated astrocytes while monitoring the activity of the surrounding network with electrophysiological recordings and calcium imaging. Stimulating a single astrocyte activates other astrocytes in the local circuit and can trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
168
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(187 citation statements)
references
References 47 publications
(63 reference statements)
18
168
0
1
Order By: Relevance
“…The physiology underlying infraslow propagation over hundreds to thousands of milliseconds is also presently unknown. This mechanistic uncertainty extends to propagation of ∼1-Hz activity over hundreds of milliseconds, where prior work has implicated factors ranging from purinergic signaling to the balance in excitatory and inhibitory activity (7,35). Future work is required to resolve these questions.…”
Section: Discussionmentioning
confidence: 99%
“…The physiology underlying infraslow propagation over hundreds to thousands of milliseconds is also presently unknown. This mechanistic uncertainty extends to propagation of ∼1-Hz activity over hundreds of milliseconds, where prior work has implicated factors ranging from purinergic signaling to the balance in excitatory and inhibitory activity (7,35). Future work is required to resolve these questions.…”
Section: Discussionmentioning
confidence: 99%
“…This means that during intense excitatory glutamatergic barrages, a release of adenosine from neurons and/or glia would assist in shortening the duration of glutamatemediated plateau potentials via the opening of K þ channels [27,[59][60][61]. The release of adenosine from neurons or glial cells can act as a protective mechanism against glutamate overstimulation in two ways: (i) by inhibiting glutamate release from presynaptic terminals and (ii) by downregulating the synaptic activity level during ischaemic-like conditions [62][63][64][65] or during an UP state in slow wave sleep [22,66,67]. It was shown that extracellular concentration of adenosine tends to escalate during seizures and after stroke, possibly as a homeostatic feedback mechanism for preventing tissue damage and by acting as an endogenous anticonvulsant [68][69][70].…”
Section: (Iii) A1 Antagonist Cptmentioning
confidence: 99%
“…The design of RuBi-GABA [18] and RuBiGlutamate [20] opened a wide spectrum of possibilities to experiment with 1P and 2P active caged versions of the most ubiquitous inhibitory and excitatory neurotransmitters. RuBi-Glutamate appears to be a superb tool to determine circuitry in dense neuronal systems [28][29][30][31][32]. On the other hand, the physiology of neuronal inhibition can be studied with the use of RuBi-GABA, the first caged GABA with 2P capabilities, necessary to address single dendritic spines [33][34][35][36].…”
Section: Applications Of Ru-bpy Complexes In Neurophysiologymentioning
confidence: 99%